Pengaruh Lama Penyimpanan Terhadap Kandungan Nutrisi Silase Ransum Komplit Berbasis Tongkol Jagung - Mita, Mita Arifa Hakim; Ichlasul Amal; Andi Muh. Fuad Alkautsar; Windiana; Irna (Jurnal Ilmu dan Industri Peternakan, 2025)
This study aims to evaluate the effect of storage duration of corn cob-based complete feed silage on changes in nutritional content, including dry matter, crude protein, and crude fiber. The study used a completely randomized design with four treatments: no storage (P1), 2 weeks of storage (P2), 4 weeks (P3), and 6 weeks (P4), each with five replicates. Data were analyzed using analysis of variance (ANOVA) and followed by Duncan's test at the 5% level. The results showed that different storage durations produced significant changes in all three nutritional components. Dry matter increased significantly from week 2 to week 6. Crude protein decreased during initial storage (up to week 2), then remained relatively stable until week 6. Crude fiber remained relatively stable until week 4 but decreased significantly by week 6. Overall, storage duration had a significant effect on the nutritional content of corn cob-based complete feed silage, with 4 weeks of storage showing a relatively more stable and optimal nutritional composition.